Noble Ideals and Bloody Realities
1 online resource.
Keywords: The contributions presented in this volume address several issues related to the topic of medieval warfare from a variety of disciplinary perspectives and examining a number of geographical regions. The contributors analyze social and economic issues, military strategy, technological and medical developments, ideology and rhetoric, and address warfare in Europe, the Byzantine Empire and the Muslim world. In three parts, the contributors explore warfare in theory, warfare in practice and warfare as perceived through medieval and modern historiography. In doing so they present a number of engaging case studies that will be of use to students and scholars interested in warfare and its effects on medieval society.